Philosophical and Legal Analysis of Factors in the Development of Ukraine's Legal Culture - Piholenko, Oleksandr (Problems of legality, 2026)
Research is dedicated to the philosophical-legal analysis of Ukraine's legal culture through the prism of historical development, which allows revealing the multidimensionality of this phenomenon in the context of forming national identity and legal consciousness. The relevance of the topic is determined by the necessity for deeper understanding of the value-based, moral, and legal foundations that determined the trajectory of Ukrainian society's development at various stages of its historical formation. The aim of the work is to clarify the key factors that influenced the evolution of legal culture, as well as to determine the peculiarities of its current state and development prospects under conditions of globalization and integration processes. The methodological foundation of the research consists of the historical-legal method, which enabled reproducing the sequence of stages in legal culture formation; the comparative method, which allowed comparing Ukrainian experience with legal traditions of other European states, as well as the axiological method, aimed at identifying the system of values that underlie legal norms and institutions. As a result, it was established that Ukraine's legal culture was formed under the influence of a combination of several key factors: national traditions and customary law, European legal standards borrowed during periods of active integration into Western civilization, and transformational processes related to changes in political regimes. State-building transformations played a special role, which were accompanied by reconceptualizing the role of law in society and changing its value orientations. Contemporary legal culture of Ukraine is distinguished by the combination of democratic and national values, enshrined in the Constitution and international obligations of the state, with residual elements of legal nihilism and paternalistic attitudes that are a legacy of previous historical epochs. Prospects for further research are seen in studying mechanisms for raising the level of legal culture through the education system and legal education, development of civil society institutions, as well as in the democratic evolution of the legal environment.